Bank Inquiry is a Means of Reducing Banking Risks - Boukhors, Abdelaziz (Journal of Legal Studies and Researches, 2017)
The bank's inquiries about its customers are one of the most important manifestations of the general commitment to the caution and carefulness that characterizes banking in the current era. This can be considered as a means for the bank to protect its interests and those of the depositors whose money are used in lending operations, as well as to protect the legitimate interests of others. In this way, the bank is professionally committed to carry out the needed inquiries on the occasion of its banking operations or the services it provides.